Noma surgery. (8th September 2018) - Shaye, David A.; Winters, Ryan; Rabbels, Jens; Adentunji, Adenyiyi Seminyu; Magee, Aidan; Vo, Daniel
Abstract : Objective: Noma is a devastating and destructive disease of the face for which there is a dearth of information regarding surgical options. Herein, we describe the facial deformities and patient characteristics in a patient population affected by noma and the surgical approaches used in treatment. Methods: Retrospective case series of a Doctors Without Borders (Médecins Sans Frontières) intervention at Sokoto Children's Noma Hospital in northern Nigeria, the highest‐volume noma hospital in the world. Results: Twenty‐two procedures were performed on 18 patients with noma, 44% of whom were children. The majority of patients (n = 10, 55.5%) were made aware of surgical care through a Doctors Without Borders outreach program. Patients' reasons for seeking care included functional (61.1%, n = 11), appearance (61.1%, n = 11), and social stigma (66.7%, n = 12). The majority (83.3%, n = 15) had lip involvement. Four patients (22.2%) underwent staged flap procedures including prelamination, flap delay, or pedicle division. The mean duration of surgical procedure was 87 minutes (range 5–306 minutes). The minor complication rate was 16%. There were no major complications or deaths. Conclusion: Noma is a mutilating disease of the face that occurs in settings of extreme malnutrition. A total of 55.5% of noma patients were made aware of surgical care through outreach programs. The majority of noma patients seek care to improve function (61.1%) and appearance (61.1%), and to address social stigma (66.7%). A total of 83.3% of noma patients had lip involvement. Facial reconstructive surgeons must rely on principles of congenital, traumatic, and oncologic deformity repair while focusing on safe, reliable procedures for low‐resource settings. Level of Evidence: 4 Laryngoscope, 129:96–99, 2019